Pandora's Box in Mappalili: Exploring Environmental Rhetoric and Cultural Communication in the Bugis Community - Giswandhani, Mariesa; Saleh, Rahmita; Saade, Abdul Rahman; Zul Hilmi, Amalia (Humaniora: Journal of Indonesia Culture and Society, 2024)
The Mappalili ritual, held before planting, is believed to help maintain ecological balance. While past studies have emphasized its cultural significance, the research shifts the focus toward environmental conservation and the role of the Bissu as communicators of environmental values through tradition. The research explored relationship between the concept of Pandora’s box and Mappalili within the framework of environmental rhetoric and cultural communication in the Bugis community, specifically in Segeri District, Pangkajene and Kepulauan Regency, South Sulawesi. The research was guided by three indicators: community awareness and participation, coordination and communication, and cultural values, using environmental rhetoric analysis. The qualitative approach included in-depth interviews with Bissu leaders and participant observation during Mappalili. The data were analyzed through environmental rhetoric theory to capture how symbolism and cultural practices contributed to ecological balance. Findings reveal that Mappalili serves as an effective tool for environmental communication, with the ritual’s symbols and values fostering harmony between humans and nature. The Bissu, as the leader, imparts ecological principles to the community, including natural farming practices that preserve soil health and minimize ecosystem harm. Disruptions or improper performance of the ritual potentially lead to negative environmental impacts, akin to opening a Pandora’s box that destabilizes the ecosystem. The research underscores the significance of preserving Mappalili as an essential environmental communication strategy, demonstrating that cultural continuity supports ecosystem sustainability. Additionally, the enduring role of the Bissu as cultural symbols in South Sulawesi reflects a deeply rooted environmental knowledge integral to this tradition.